The 'origins of football debate' and the early development of the game in Nottinghamshire. (10th November 2017) - Curry, Graham; Dunning, Eric
Abstract : This article continues the debate on the origins of football. It contains new data which note early football activity and initial club formation in Nottinghamshire. The authors reach the conclusion that former public schoolboys were prominent in the development of football in that particular area and see this as further confirmation of their hypothesis that many of these individuals should be seen as important in the establishment of football as a modern sport.